Evaluasi Hukum Kontrak Waralaba Dalam Pendekatan Hukum Perdata - Laura Sharendova Gunawan; Urbanisasi Urbanisasi (Peneliti.net, 2023)
This study was conducted to learn more about the characteristics of the franchise industry and how it develops in relation to the rapid development of the franchise industry in Indonesia. According to the findings of the study, the franchise industry is still largely unknown among Indonesians even though it is a more profitable and capital-efficient business model than starting a new business. With certain rights and obligations carried out by each party based on the terms of the agreement set forth in the Civil Code, this franchise business can be launched immediately after an agreement is reached between the owner of the franchise right and the holder of the franchise right. However, apart from the basic contractual terms, the government-specific laws and regulations that serve as the legal framework for the growth of this franchise business are still sorely lacking. As a result, many entrepreneurs continue to be